First Insight of Meso- and Bentho-Pelagic Fish Dynamics Around Remote Seamounts in the South Atlantic Ocean - Campanella, Fabio; Collins, Martin A.; Young, Emma F.; Laptikhovsky, Vladimir; Whomersley, Paul; van der Kooij, Jeroen (Frontiers in Marine Science, 2021)
Seamounts have long been recognised as hotspots for pelagic productivity and diversity in the world’s open ocean habitats. Recent studies have suggested that productivity may vary greatly between different seamounts, depending on complex interactions between the bathymetric features and local oceanography. These processes may enhance local primary production which support elevated biomass at higher trophic levels. In addition to enhancing local biomass, seamounts may also act as aggregative features, attracting pelagic species from the surrounding waters. Such characteristics make seamounts attractive targets for fisheries. However, as these unique habitats are localised and relatively small, they are vulnerable to overexploitation, which may have detrimental impact on the wider region. Mapping and quantitative assessments of the fish biomass at different seamounts are crucial prerequisites to identifying vulnerable seamounts and will aid toward understanding the dynamics of these important ecosystems and their vulnerability to fishing pressures. We used fisheries acoustics during two expeditions in 2018 and 2019, to investigate the distribution and abundance of fish and micronekton on and around five little studied seamounts of Tristan da Cunha, a remote archipelago in the South Atlantic Ocean. The results confirmed increased productivity at the seamounts, compared to the surrounding open ocean with higher acoustic backscatter values, a proxy for biomass, particularly at the shallower (~200 m depth) seamounts. Fish largely dominated the backscatter on most of the seamounts especially over the plateau areas where large densities of prey fish, primarily the mesopelagic Maurolicus inventionis, were detected. Very large aggregations, thought to consist of bentho-pelagic fish, were also observed over the slope of McNish Seamount that resulted in very high biomass estimates. Aggregations of this size and magnitude, have, to our knowledge, never been mapped or quantified on seamounts, using acoustic methods. Specific physical processes, such as enhanced retention and vertical mixing that were identified by an oceanographic model, may be some of the drivers of the enhanced fish biomass detected at McNish. The characteristics of the seamounts observed in this work suggest that these habitats are highly suitable for the presence of large predatory fish that can utilise these areas as their primary habitat or as important foraging grounds.